Black, White and Blue: Pregnancy and Unsettled Binaries in The Masque of Blackness (1605) - Pascale Aebischer; Victoria Sparey (Multicultural Shakespeare, 2020)
This article examines the construction of national and racial identities within Ben Jonson’s and Inigo Jones’s Masque of Blackness against the backdrop of King James’ investment in creating a ‘British’ union at the start of his reign. The article re-examines the blackface performance of the Queen and her ladies in the contexts of the Queen’s and Inigo Jones’ European connections, the Queen’s reputation as ‘wilful’, and her pregnant body’s ability to evoke widespread cultural beliefs about the maternal imagination’s power to determine a child’s racial make-up. We argue that the masque’s striking use of blue-face along with black and white-face reveals a deep investment in Britain’s ancient customs which stands in tension with Blackness’ showcasing of foreign bodies, technologies, and cultural reference points. By demonstrating the significance of understanding Queen Anna’s pregnancy and her ‘wilful’ personality within the context of early modern humoral theory, moreover, we develop existing discussions of the humoral theory that underpins the masque’s representation of racial identities. We suggest that the Queen’s pregnant performance in blackface, by reminding the viewer that her maternal mind could ‘will’ the racial identity of royal progeny into being, had the power to unsettle King James I’s white male nationalist supremacy in the very act of celebrating it before their new English court and its foreign guests.